THE STRATEGY OF YOUNG’S FAMILY TO CLAIM AS THE RICHEST FAMILY IN KEVIN KWAN’S NOVEL CRAZY RICH ASIAN - Suma Ningtyas, Chinintya (Universitas Hasanuddin, 2017)
This article aims to reveal the strategy of Young’s family to maintain the social class as an Asian jetset family. The Young’s family uses their social status by revealing their power in explicitly or implicitly strategy. The problem focuses on how the Young’s family negotiates their legitimation of social status and the perspective of Kevin Kwan as the author of the novel. This article signifies the use of the Bordieu’s concept: habitus, capital, and modal. By using the Bordieu’s perpective, the writer is able to find the picture of high class society which full control of the capital, cultural, social, and also their habitus. In this article, Kevin also implies on his novel the representation of glamourous lifestyle of hish class family in Asia.Keywords: Keyswords: Bordieu, strategy, capital, habitus, modal, social class